(untitled) (Bangladesh Journal of Pharmacology, 2012)
The effect of methanol extract of Prosopis cineraria against experimental liver tumor in rats was studied. Liver tumor was induced by the administration of N-nitrosodiethylamine (200 mg/kg) and it was promoted by phenobarbital administration. Methanol extract (200 and 400 mg/kg) was administered to determine the protective activity. Administration of methanol extract suppressed the liver tumor effectively as revealed by the decrease in elevated levels of aryl hydrocarbon hydroxylase, lactate dehydrogenase, g-glutamyl transpeptidase (g-GTP), 5nucleotidase, deoxyribonucleic acid (DNA) and ribonucleic acid (RNA). We found that methanol extract may extend its protective role by modifying the levels of marker enzymes and nucleic acid contents.